2022
DOI: 10.4236/ajps.2022.132014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Auxin and Cytokinin on <i>in Vitro</i> Shoot Regeneration and Rooting of Endangered Medicinal Plant <i>Valeriana jatamansi</i> Jones through Tissue Culture

Abstract: Micropropagation of Valeriana jatamansi Jones by using small segments of rhizome on full strength MS medium having various concentrations and combinations of auxin Naphthaleneacetic acid (NAA) and cytokinin Benzylaminopurine (BAP) was conducted. The highest mean shoot length (3.71 cm) was achieved when media was fortified with BAP 2 mg/L in combination with NAA 1 mg/L. The highest mean leaf number i.e. 6.00 was observed when BAP was used alone at 2 mg/L. Average root length (0.77 cm) was recorded when BAP 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
2
0
2
Order By: Relevance
“…These observations align with previous studies in plant micropropagation that have reported IBA and NAA as suitable for root induction and optimal root length at low auxin concentration levels (Aroonpong and Chang 2015;Nazir et al 2022;Hejazi et al 2023).…”
Section: In Vitro Rootingsupporting
confidence: 91%
“…These observations align with previous studies in plant micropropagation that have reported IBA and NAA as suitable for root induction and optimal root length at low auxin concentration levels (Aroonpong and Chang 2015;Nazir et al 2022;Hejazi et al 2023).…”
Section: In Vitro Rootingsupporting
confidence: 91%
“…These results are consistent with those of Sreekissoon et al (2021) who found that IBA was the most suitable auxin for root formation from nodal explants of Sceletium tortuosum. Auxin acts by attaching to a receptor protein and initiating a signaling cascade that most likely includes the proteolysis of transcription regulators (AUX/IAA) through the ubiquitin-proteasome system, which un-represses genes (Nazir et al, 2022). Furthermore, given that auxin has been demonstrated to play a key role in rooting apical organizing, it is conceivable to interpret the auxin oscillations from induction throughout formation as potentially connected to apical organizational processes (Nadal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The results of another study indicated that MS medium with 0.5 mgL -1 BAP and 0.25 mgL -1 IBA was the optimum medium for in vitro shoot multiplication of rodent tuber (16 shoots in 6 weeks) [27]. In the micropropagation of the medicinal plant Valeriana jatamansi Jones utilizing rhizome explants, it was discovered that adding BAP up to 1 -2 mgL -1 increased shoot length, number of leaves, and leaf growth when used in combination with NAA at 0-1 mgL -1 [28]. This is consistent with research on the P14 treatment (50 ppm BAP and 25 ppm NAA), which produced 8.10 shoots.…”
Section: The Effect Of Pgr Bap and Naa Combination On Rodent Tuber Sh...mentioning
confidence: 99%